The Organizational Culture Role and VOD Interaction for the Improvement of Company Competitive Advantage in Management Perspective - Suhendri SUHENDRI; Yeni ABSAH; Elisabet SIAHAAN; Sirojuzilam SIROJUZILAM (Communications of International Proceedings, 2023)
This study aims to prove the role of Organizational Culture (OCR) and Value Oriented Development (VOD) interaction on Company Competitive Advantage (CCA) from a management perspective.  This research used a quantitative study with survey instruments. The survey was conducted by 433 officials at the strategic and operational management levels. The sampling method is the census method. Data analysis used a modeling approach called Structural Equation Modeling. The statistical tool used is Lisrel 8.8. The finding of studi is  The role of organizational culture was not significant to the company's competitive advantage. However, the increase in the ability of VOD interaction had a significant effect. Another finding is that the company's competitive advantage was proven to be significantly influenced by the company's VOD interaction capabilities. From the point of view of the Resources Based Theory (RBT) approach, according to management, a company's competitive advantage is greatly influenced by the company's VOD interaction ability in optimizing resource utilization. Meanwhile, the role of corporate culture is very important to improve the company's VOD capability in achieving competitive advantage.  This research provides a new perspective showing that the role of organizational culture directly does not have a significant influence in increasing the company's competitive advantage. But the role of culture has a significant impact on the company's VOD interaction capabilities. VOD interaction is a major determinant factor of a company's ability to be superior to its competitors.
Keywords: Organizational Culture Role; Value Oriented Development; Company Competitive Advantage.